Muon (g − 2) and the W-boson mass anomaly in a model based on Z4 symmetry with a vector-like fermion. (4th November 2022) - Arora, Simran; Kashav, Monal; Verma, Surender; Chauhan, B C
Abstract: The latest results of the CDF-II Collaboration show a discrepancy of 7σ with standard model expectations. There is also a 4.2σ discrepancy in the measurement of the muon magnetic moment reported by Fermilab. We study the connection between neutrino masses, dark matter, the Muon ( g − 2) experiment, and the W-boson mass anomaly within a single coherent framework based on a Z 4 extension of the scotogenic model with a vector-like lepton (VLL). Neutrino masses are generated at the one-loop level. The inert doublet also provides a solution to the W-boson mass anomaly through correction in oblique parameters S, T, and U . The coupling of the VLL triplet ψ T to the inert doublet η provides a positive contribution to the muon anomalous magnetic moment. In the model, the VLL triplet provides a lepton portal to dark matter, η _R^0 . The model predicts a lower bound mee > 0.025 eV at 3σ, which is well within the sensitivity reach of the 0νββ decay experiments. The model explains the muon anomalous magnetic moment Δ a μ for 1.3 < y ψ < 2.8 and a DM candidate mass in the range 152 GeVM_η _R^0195 GeV . The explanation of the W-boson mass anomaly further constrains the mass of the DM candidate, M_η _R^0, in the range 154 GeVM_η _R^0174 GeV .